PENGARUH BUDAYA ORGANISASI DAN EMPLOYE ENGGAMENT TERHADAP KINERJA KARYAWAN PADA PT. BUMI MINERAL SULAWESI - Yunus Yunus; Muhammad Kasran; Suparni Sampetan (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to examine and analyze the influence of organizational culture and employee engagement on employee performance at PT. Sulawesi Mineral Earth. The sample in this study consisted of 70 respondents. the hypothesis was tested with multiple linear regression analysis using the SMART PLS Application. The results of the research on the influence of organizational culture on employee performance have a significant positive effect on employee performance, employee engagement has a positive effect on employee performance. Keywords: organizational culture, employee engagement, and employee performance